Health-Related Quality of Life in Patients with Friedreich Ataxia Using Mobility Assistive Technologies: Limited Fit of the EQ-5D-3L Mobility Dimension - Maresa Buchholz; Michelle Pfaff; Audrey Iskandar; Kathrin Reetz; Jörg B. Schulz; Marcus Grobe-Einsler; Thomas Klockgether; Bernhard Michalowsky; EFACTS Study Group (Neurology and Therapy)
Abstract Introduction Friedreich Ataxia (FA) is a multisystem neurodegenerative disease. Affected individuals rely on mobility assistive technologies (MAT) (e.g. wheelchairs) and require long-term treatments and care. To analyse the patients’ health-related quality of life (HRQoL), the EuroQol 5 Dimension 3 Level survey (EQ-5D-3L)—a widely used and recommended generic measure—is used in clinical and in health economic studies. Concerns about using the instrument in mobility-impaired individuals who might have difficulties finding appropriate response options for mobility-related items led us to investigate how the 3L dimensions perform in patients with FA using or not using MAT. Methods Using longitudinal data from 607 patients with FA of the EFACTS study (from baseline to the 3-year follow-up), we analysed the acceptability, distribution properties, validity, and responsiveness of the EQ-5D-3L, focusing on the mobility item. Analyses were stratified for patients without and with different MAT-usage. Results We identified that n = 177 patients used no MAT, n = 299 a wheelchair and n = 131 walking aids. The mobility item non-response was highest in wheelchair users (6.8%) and lowest in patients without MAT. Walking aid users showed the least variability, all selecting the mid-response option “some problems” for mobility. The mobility item correlated moderately with disease severity (r sp = 0.35) and the activities of daily living scale (r sp = 0.36) in wheelchair users. No correlation exists for walking aid users. The strongest health changes occurred for wheelchair users, the weakest for walking aid users. The mobility dimensions showed the highest amount of no changes. Conclusion The EQ-5D-3L’s mobility item has limitations in MAT users, particularly in walking aid users, due to a tendency towards mid-responses. These limitations may affect the efficacy and (cost)effectiveness conclusions drawn from interventions and clinical trials with mobility-impaired individuals. Further research is needed to explore the understanding and interpretation of responses of the EQ-5D in patients with FA with mobility support. Trial Registration ClinicalTrials.gov identifier NCT02069509.